Academic stress and brain fog in COVID-19 survivor students - Sejati, Inna Indah; Sunarya, Chiyar Edison (Universitas Muhammadiyah Semarang, 2024)
COVID-19 is an infectious disease caused by the SARS Cov-2 virus. Covid-19 caused a pandemic that has been going on since 2020. Since the pandemic, many people have been confirmed, and many have recovered who are said to be survivors of COVID-19. COVID-19 survivors can still experience symptoms such as brain fog. Students as survivors of COVID-19 who do learning can feel stress; the stress they get is called academic stress. This research was conducted to find a relationship between academic stress and brain fog in students who survived COVID-19. This study used a cross-sectional design involving 125 student survivors of COVID-19. Data analysis showed that 49 students (39.2%) did not experience brain fog, while 76 students (60.8%) were suspected of experiencing brain fog. Spearman's rank correlation test also showed a correlation between academic stress levels and brain fog (p value = 0.000) in students who survived COVID-19 with an r value of 0.409. The incidence of brain fog in COVID-19 survivors is deemed to be influenced by academic stress. There needs to be good stress management for students who are survivors of COVID-19 to maintain their thinking skills.